1985
DOI: 10.1159/000233712
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Synthesis of IgE by Human Peripheral Blood Leucocytes

Abstract: The assessment of IgE production in cultures of T- and B-cells from peripheral blood is proving a useful tool to probe IgE immunoregulation in human atopies. The present study contrasts secretion and synthesis as indices of IgE production, and demonstrates that these measures yield comparable data upon the magnitude and direction of regulatory T-cell effects (help vs. suppression) in severe atopies. The majority of peripheral blood B-cell samples from the atopies in this study exhibited spontaneous IgE synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 3 publications
(3 reference statements)
4
27
0
Order By: Relevance
“…In this context, the average serum content of IgG in these patients was 11.8 mg/ ml, which represents a 10,000-fold excess over their serum IgE levels (1.01 qg/ml). However, when cellassociated levels of lg were calculated as described by Turner et al [18], the content of IgG in 6 samples (23.8 ± 8.8, range 15.37 ng/ml) was in excess of that of IgE (688 ±591, range 127-1,731 pg/ml) by only a fac tor of 34.6. Consequently, uptake of the IgE isotype by monocytes is unlikely to be via random pinocytosis, but must instead involve a highly selective mechanism.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this context, the average serum content of IgG in these patients was 11.8 mg/ ml, which represents a 10,000-fold excess over their serum IgE levels (1.01 qg/ml). However, when cellassociated levels of lg were calculated as described by Turner et al [18], the content of IgG in 6 samples (23.8 ± 8.8, range 15.37 ng/ml) was in excess of that of IgE (688 ±591, range 127-1,731 pg/ml) by only a fac tor of 34.6. Consequently, uptake of the IgE isotype by monocytes is unlikely to be via random pinocytosis, but must instead involve a highly selective mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…We have recently reported that enriched pop ulations of human monocytes/B cells from atopies contain significant levels of acid-extractable IgE [18][19][20], which is secreted in active form during in vitro culture. Much of this is performed and does not arise by de novo synthesis in vitro by B cells, and thus presumably represents IgE released from the mono cyte pool (as shown in figure 1) via exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several at tempts have also been made to establish whether the spontaneously IgE-producing cells detected in the cir culation of atopies are still sensitive to the influence of modulatory signals delivered in vitro. The addition of lectins, such as pokeweed mitogen (PWM), to cul tures of MNC from atopies and, more consistently, to B cell enriched populations induced suppression of the spontaneous IgE production [8,11,12], Likewise, pre-incubation of cells from grass-sensitive or mitesensitive patients with grass or mite antigen, respec tively, as well as the addition to cultures of anti-IgE monoclonal antibodies, appeared to be consistently inhibitory on the spontaneous IgE production in vitro [13][14][15], The effect of autologous or allogeneic T cells on the spontaneous IgE production in vitro by atopic B cells has also been investigated. In some patients with severe atopic disease T cells had inhibitory activity on the IgE production by autologous B cells; in some pa tients the inhibitory activity exerted by autologous T cells was radioresistant, while in other patients it was radiosensitive.…”
Section: In Vitro Spontaneous Ige Productionmentioning
confidence: 99%
“…IgE determinations were performed as described by Turner et al (9), modified by the use of a polyclonal rabbit anti-IgE as the capture antibody on the paper discs and a mouse monoclonal anti-IgE (2.1.5) as the radiolabelled detector antibody. Both antisera were prepared in our laboratory.…”
Section: Determination Of Ige Production In Vitromentioning
confidence: 99%
“…vitro correlate with these in vivo observations, utilizes in vitro synthesis of IgE by peripheral blood leucocytes (PBL) from atopic donors (6)(7)(8)(9). A number of authors (4,(10)(11)(12)) demonstrated with this model that while de novo synthesis, as opposed to secretion (13), of pollen-specific IgE, was relatively low, it only occurred in cultures of PBL collected during the pollen season.…”
Section: Introductionmentioning
confidence: 96%